Modern diplomacy - Barston, R. P. (Ronald Peter) (Abingdon, Oxon ; New York, NY : Routledge, Taylor and Francis Group, 2019)
Contemporary, thoughtful and extensively illustrated, Modern Diplomacy examines a broad range of current diplomatic practice. This leading and widely used book - now in its fifth edition - equips students with a detailed analysis of important international issues that reflect and impact upon diplomacy and its relations. The subject is brought to life through case studies and examples which highlight the working of contemporary diplomacy within the international political arena. Organised around five broad topic areas, including the nature of diplomacy, diplomatic methods, negotiation, the operation of diplomacy in specific areas and international conflict, the book covers all major topic areas of contemporary diplomacy. New features for this edition: Developments in diplomatic practice Strategies in diplomacy International trade, geopolitics and agreements Diplomacy of new regional organisations and groupings Developing country diplomacy Non-traditional diplomacy New concepts - parallel and counter diplomacy New case studies include: the Paris Climate Agreement, Brexit, international finance and trade agreements, and the UN security forces. Modern Diplomacy is essential reading for students and practitioners of international relations, foreign policy, international law, international political economy, international economics, the Foreign Services Institutes and the National Diplomatic Academies.
16 The diplomacy of normalisation17 Diplomatic correspondence: case examples; 18 International treaties; 19 International agreements: case examples; 20 The Paris agreement; 21 Conclusion; Index
OCLC-licensed vendor bibliographic record.
Keywords: Diplomacy; POLITICAL SCIENCE / Government / International; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / General; POLITICAL SCIENCE / International Relations / Diplomacy